1996
DOI: 10.1128/aem.62.5.1781-1787.1996
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of different Listeria ribotypes from naturally contaminated, raw refrigerated meat and poultry products with two primary enrichment media

Abstract: Isolation rates for Listeria monocytogenes and the other Listeria spp. typically improve when samples are enriched in more than one primary enrichment medium. This study evaluated the abilities of two primary enrichment media, University of Vermont-modified Listeria enrichment broth (UVM) and Listeria repair broth (LRB), to recover different ribotypes of Listeria spp. from raw meat and poultry samples. Forty-five paired 25-g retail samples of ground beef, pork sausage, ground turkey, and chicken (160 samples) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 37 publications
4
33
0
1
Order By: Relevance
“…Indeed, different strains can be isolated from the same sample by an enrichment procedure and a direct plating ( P h i and Gilbert 1988;Loncarevic rt al. 1996) or by different enrichment media (Ryser et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, different strains can be isolated from the same sample by an enrichment procedure and a direct plating ( P h i and Gilbert 1988;Loncarevic rt al. 1996) or by different enrichment media (Ryser et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These different strains have been isolated from foods by two methods, an enrichment procedure and a direct plating procedure. Molecular typing methods including restriction enzyme analysis, pulsed-field gel electrophoresis and ribotyping, have recently been used to characterize and compare L. monoqytogenes strains isolated from the same food sample (Loncarevic et al 1996;Ryser et al 1996). T h e results suggest that the ability to recover specific Listeria strains is at least partially dependent on the enrichment procedure and the picking of a sufficient number of colonies per sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, ribotyping, regardless of the probe used, cannot accurately distinguish between serovar 4b strains, a serovar responsible for major foodborne outbreaks of listeriosis, as previously observed (4,16,25,26). Despite this, a major advantage of this method is the automation of the procedure (1,7,17,30).…”
Section: Comparison With Pba2 Ribotyping Dna Macrorestriction Pattermentioning
confidence: 92%
“…For example, DI increases if ribotyping is combined with RAPD (4), restriction enzyme electrophoresis (REA) or multilocus enzyme electrophoresis (MEE) (26). Ribotyping is appropriate for ecological studies (1,21,30), but should be replaced by DNA macrorestriction pattern analysis for epidemiological investigations of human foodborne listeriosis, in which it is essential to identify the epidemic clone as accurately as possible so as to identify food vehicles, in conjunction with a case-control study.…”
Section: Comparison With Pba2 Ribotyping Dna Macrorestriction Pattermentioning
confidence: 99%
“…It can also survive freezing (Gola et al 1990). These micro-organisms, which are generally associated with dairy products, have been detected in a wide variety of foods, such as raw meat (Donnelly 1994;Ryser et al 1996), cheese (Szczawinski et al 1997), different pasteurized products (Fernández Garayzabal et al 1986;Yen et al 1994), and even in vegetable products (Heisick et al 1989). Conner et al (1986) found L. monocytogenes in marrow and showed that this could be transmitted to humans.…”
Section: Introductionmentioning
confidence: 99%